Cutaneous cysts: a clinicopathologic analysis of 2, 438 cases. (7th February 2020) - Kamyab, Kambiz; Kianfar, Nika; Dasdar, Shayan; Salehpour, Zahra; Nasimi, Maryam
Abstract: Background: Benign cutaneous lesions, so‐called cysts, are frequently seen in clinics and might evoke cosmetic and psychosocial concerns. Aim: This study aimed to demonstrate the clinicopathologic findings of these lesions and also the importance of histological evaluation for prevention of misdiagnosing a benign‐appearing malignant lesion. Methods: A descriptive study was conducted of 2, 438 cases who had a diagnosis of cyst confirmed with pathology. The data of patients over the 6‐year period between 2011 and 2017, including gender, age, location, prevalence, complications, and microscopic evaluation, were gathered. Results: From a total of 2, 438 records with a clinical diagnosis of mucocutaneous cyst, 2077 had the pathologic diagnosis of cysts. They consisted of 910 women (43.8%) and 1167 men (56.1%) with a mean age of 42. The most common mucocutaneous cysts were epidermal cyst 994 (47.8%) followed by trichilemmal cyst 495 (23.8%). In 479 (19.6%) records, the clinical diagnosis was not congruent with histopathological diagnosis including 45 malignant cases. Basal cell carcinoma in 22 (48.9%) was the most common one. Conclusions: This study reports on clinical characteristics of cutaneous cysts and the need for a decent diagnostic investigation, like histopathology, for achieving a reliable diagnosis regarding the benign mimicking malignant lesions, especially high risk ones.